ANALYSING DEMOGRAPHIC TRENDS AND VISITORS SATISFACTION AT THE NATIONAL MUSEUM, DELHI (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: As demographics shifts continue, the National Museum in Delhi consistently adapts to ensure visitor  satisfaction through diverse and enriching experiences. The study at the National Museum in Delhi delves into visitor  demographics, preferences, and satisfaction, aiming to answer three primary research questions regarding visitor  expectation, personalization, and satisfaction while pursuing three key objectives through exp loring the  interplay among these factors. Objectives: To assess the alignment between visitor expectations and experiences,  identifying contributing factors, to evaluate the extent of personalization at the museum and propose enhancement  strategies, to investigate the impact of improved personalization on visitor satisfaction, aiming to achieve key study  objectives. Methodology: A quantitative approach was employed, utilizing surveys to gather data from a sample of 100  museum visitors in Delhi. Structured questionnaire focused on visitor demographics, motivations, satisfaction level, and  feedback. Canonical Correlation Analysis (CCA) and regression analysis were used for data analysis. Results: Visitors’  profile, indicating a predominant age group of 35-44 years comprising 28%, while most visitors hold Bachelor degree  at 37%. Additionally, the survey reveals that 40% of respondents visit National Museum occasionally, followed by 30  % who visit rarely. No statistically significant influence of visitor characteristics or behaviours on the museum’s ability  to cater to a diverse audience is found. Conclusion: The research provides valuable insights into visitor experiences  and behaviours at the National Museum in Delhi. Despite limitations such as a small sample size and cross-sectional  nature, the findings lay a foundation for understanding factors shaping visitor experiences. Practical implications are  discussed for enhancing satisfaction and personalization efforts, with a call for further research to consider larger and  more diverse samples and different variables.
Keywords: Visitor expectations; Visitor Satisfaction; Visitor Experience; Personalization; National Museum